1995
DOI: 10.1002/bscb.19951040911
|View full text |Cite
|
Sign up to set email alerts
|

Diphenylacetylene from the Base‐Catalyzed Fragmentation of 3,6‐Dihydro‐5,6‐Diphenyl‐3‐Tosyl‐1,3,4‐Oxadiazin‐2‐One

Abstract: Treatment of 3,6-dihydm-5,6-diphenyl-3-tosyl-I , 3,4-oxadiazin-2 ter than 70% yield.In the context of our work on 3-pyrazolidinones (1) and the related 3-oxopyrazolidinium ylides (2),' we had been interested in tetrahydro-1,3,4-oxadiazin-2-ones (3) which differ from 3-pyrazolidinones only by the presence of an oxygen in the ring. To our knowledge, the investigations of Rosenblum and his group2 remain the only report in that area. In both cases, it is likely that the cyclic a-carbonylazo intermediates,*-3 resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…We concluded that, if we could develop a direct conversion of acyloins into alkynes, a highly flexible two-step approach for the fragment coupling synthesis of internal alkynes would result. ,, We furthermore hypothesized that achieving this target reaction would require us to couple the alkyne formation to the formation of highly stabilized species, in order to ensure an overall favorable energetic profile. Indeed, the groups of Rosenblum, Marshall Wilson, and Anselme have reported the formation of tolane 1a from substrate 3 , which proceeds through the base induced formation of intermediate 4 and a subsequent thermal fragmentation leading to nitrogen and carbon dioxide as byproducts (Scheme B). Although in these studies substrate 3 was synthesized through different approaches, we wondered if it would be possible to generate this species from benzoin 2a by treatment with tosylhydrazine and a suitable carbonate-derived electrophile such as carbonyl diimidazole (CDI) …”
Section: Introductionmentioning
confidence: 99%
“…We concluded that, if we could develop a direct conversion of acyloins into alkynes, a highly flexible two-step approach for the fragment coupling synthesis of internal alkynes would result. ,, We furthermore hypothesized that achieving this target reaction would require us to couple the alkyne formation to the formation of highly stabilized species, in order to ensure an overall favorable energetic profile. Indeed, the groups of Rosenblum, Marshall Wilson, and Anselme have reported the formation of tolane 1a from substrate 3 , which proceeds through the base induced formation of intermediate 4 and a subsequent thermal fragmentation leading to nitrogen and carbon dioxide as byproducts (Scheme B). Although in these studies substrate 3 was synthesized through different approaches, we wondered if it would be possible to generate this species from benzoin 2a by treatment with tosylhydrazine and a suitable carbonate-derived electrophile such as carbonyl diimidazole (CDI) …”
Section: Introductionmentioning
confidence: 99%